CE-12 Comparison of classification criteria, self-assessments and immunologic profiles in patients with incomplete and systemic lupus erythematosus. (31st August 2016) - Olsen, Nancy J; McAloose, Carl; Carter, Jamie; Han, Bobby Kwanghoon; Raman, Indu; Li, Quan-Zhen; Liao, Duanping
Abstract : Background: The syndrome of incomplete lupus erythematosus (ILE) likely includes individuals at risk for development of systemic lupus erythematosus (SLE). Studies of interventions to lower risk or prevent further disease in ILE are of interest. Design of such trials will require methods to classify patients and to assess risk. The goals of the present study were to evaluate performance of updated SLE classification criteria to define ILE and to probe for other features in these patients that might be useful as indicators of disease status. A long term goal is to develop prognostic multifaceted risk profiles that would have clinical applications. Materials and methods: Patients with ILE (N = 70) and SLE (N = 32) defined by the 1997 American College of Rheumatology (ACR) criteria were then reclassified using the 2012 Systemic Lupus International Collaborating Clinics (SLICC) criteria. Disease activity, patient self-assessments and levels of autoantibodies, soluble mediators and expressed Type I interferon (IFN) genes also were measured in the ILE and SLE patients and compared to healthy control (HC) individuals. Results: The two sets of classification criteria were highly correlated (Figure 1 ; R 2 = 0.87). ILE patients were older (P = 0.0043), with lower SLEDAI scores (P = 0.023) and greater dissatisfaction with their health status (P = 0.034) than SLE patients. Anti-C1q and sCD27 levels were correlated with ACR criteria and SLE Disease Activity Index (SLEDAI) scores (P ≤ 0.0004). Three cytokines, IL-7, IL12p70 and IL-13, were lower in both ILE and SLE than in HCs. Two IFN-related cytokines IP = 10 and MCP-1, were higher in SLE than in ILE. Of three IFN genes measured, IFI27 showed the greatest difference between ILE and SLE. Conclusions: The 2012 SLICC SLE classification criteria likely can be used to define ILE in future research trials. Patients with ILE are somewhat dissatisfied with their condition, possibly related to anxiety about the lack of a clear diagnosis. Further patient-reported outcome studies in this population would be of interest. Reliable assessment of lupus risk will likely include demographic, clinical and immunologic features. Some of the latter may suggest novel approaches to early treatment. Acknowledgements: This project was funded, in part, with a grant from the Pennsylvania Department of Health using Tobacco CURE Funds. The Department specifically disclaims responsibility for any analyses, interpretations or conclusions. It was also?supported in part by the National Institutes of Health, NIAMS U34 AR067392. The data entry assistance of Fan He is appreciated.